Chercheurs de dieux dans l'espace public - Frontier Religions in Public Space - Pauline Côté (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2001)
By their nature, emerging religions explore unfamiliar territory and probe unchartered regions of human creativity. For these same reasons, religious transactions that venture beyond the boundaries of traditional religious frontiers often rouse suspicion, anxiety or even fear among the general population. As new religious movements seek to carve out their own niche in society, public controversy and opposing beliefs can spark bitter debates, and can even lead to calls for state intervention. How then do new or borderline religious groups negotiate or mediate the building of public space? What impact can the media have on new religions? How does the law withstand the "creative destruction" of religious innovation? In this provocative collection of essays, twelve experienced specialists break new ground in the sociological study of religion.